THE FORMATION OF THE CORPORATE BOND MARKET IN UKRAINE WITH THE AIM OF ATTRACTING INVESTMENT AND ENTERPRISE RESOURCE - S. V. Kalambet; S. V. Kalambet (Nauka ta progres transportu, 2009)
The domestic experience of attracting the financial resources at an enterprise is analyzed. The opportunities and restrictions re. attracting the means by public enterprises are considered. Starting from the restrictions of public enterprises re. attracting the financial resources, the recommendations on advisability of alternative forms of crediting the activities of enterprises such as internal obligation loan are developed.